Practice effects of personalized interventions with interdisciplinary teamwork in type 2 diabetes remission: a retrospective study - Tian, Xiaona; Tang, Yujin; Hu, Rongrui; Ye, Jianhong; Chen, Haixin; Wu, Junjie (Frontiers in Endocrinology, 2024)
Objectives: A retrospective analysis of the clinical outcomes of personalized interventions for type 2 diabetes mellitus (T2DM) in an interdisciplinary team. Methods: Under the guidance of an interdisciplinary team, 40 patients with T2DM underwent a systematic examination at the beginning of the intervention, 3 months after the intervention, and 3 months of follow-up at the end of the intervention (i.e., at 6 months). Key indicators such as fasting plasma glucose (FPG), 2-hour postprandial glucose (2hPG), fasting insulin level (FINS), glycated hemoglobin (HbA1c), blood lipids, and body mass index (BMI) were measured. Results: After the 3-month intervention, participants' BMI, FPG, 2hPG, FINS, and HbA1c improved significantly, with statistically significant differences (P<0.05).These metrics remained essentially stable at the 3-month follow-up. Of all the participants, 92.5% (37 cases in total) successfully discontinued their medication after 3 months of intervention, of which 80% (32 cases) remained stable during the 3-month follow-up after discontinuation, fulfilling the criteria for remission of T2DM; 2 cases successfully reduced the dose of their medication, and only 1 case was maintained on the original treatment. Conclusions: Through an interdisciplinary team intervention strategy, we significantly optimized the glucose metabolism, lipid metabolism, and BMI status of patients with T2DM, making diabetes remission an achievable goal, which provides valuable experience for further optimization of diabetes prevention and control protocols. Keywords：Interdisciplinary . Type 2 diabetes . Personalized interventions . Diabetes remission